Encounter : a novel of nineteenth-century Korea - Han, Mu-suk, 1918-1993 (Voices from Asia ;, 1992)
This historical novel, Encounter (Mannam), by Hahn Moo-Sook, one of Asia's most honored writers, is a story of the resilience in the Korean spirit. It is told through the experiences of Tasan, a high-ranking official and foremost Neo-Confucian scholar at the beginning of the nineteenth century. Because of Tasan's fascination with Western learning, then synonymous with Catholicism, he is exiled to a remote province for 18 years. In banishment he meets people from various social and religious backgrounds-Buddhist monks, peasants, shamans-whom he would not otherwise have met. The events of Tasan'